Computational simulation of the ore-forming processes associated with the Sanshandao-Haiyu gold belt, Jiaodong Peninsula, eastern China: implications for the duration of ore formation - Shan, Wenfa; Mao, Xiancheng; Liu, Zhankun; Deng, Hao; Tang, Lei; Wang, Dutao; Pan, Yong; Liu, Yao (Frontiers in Earth Science, 2023)
The Sanshandao-Haiyu gold belt, Jiaodong Peninsula, Eastern China accounts for more than 1400 t gold resources, which is always recognized as a coupled result of structural deformation, pore-fluid flow, and hydrothermal alteration-mineralization processes. However, the ore-forming processes associated with this gold belt has not been fully understood by the coupled perspective. In this paper, we use computational modeling to study the spatial distribution of dilation (positive volumetric strain) and the mineralization rate, which can predict the mineralization patterns from a chemical perspective, so as to solve the fully coupled problem during ore-forming processes. The model was loaded on the FLAC3D platform to test four scenarios: (1) syn-compression in the NW-SE direction; (2) syn-compression in the WNW-ESE direction; (3) syn-compression in the NNW-SSE direction, and (4) syn-extension in the NW-SE direction. The simulation results show that only the syn-compressional scenario can produce wide dilation zones with a distribution pattern similar to the known orebodies. The higher dilation zones with the volumetric strain (>0.1 %) and the highest pore-fluid flux are closely associated with the fault geometry, particularly for the gentle segments near the steep-flat transition areas. Besides, the dilation zones also occur with very high absolute values of pore-fluid pressure gradient and temperature gradient, indicating significantly perturbed physical-chemical conditions. The receiver operating characteristic (ROC) curves of the mineralization rate show that the area under the curve (AUC = 0.862) of the NW-SE syn-compression model is the highest among these four scenarios, indicating a major paleo compression stress direction of NW-SE during ore-forming period. Furthermore, based on the mineralization rate, we estimated that the mineralization duration of the Sanshandao-Haiyu gold belt would be less than 100,000 years. These simulation results can not only enhance our understanding of the ore-forming processes in the Sanshandao-Haiyu gold belt and Jiaodong Peninsula but also demonstrate that these can be used directly or indirectly for deep mineral exploration.